The LUDIC OF REFLECTION IN PHYSICAL EDUCATION SCHOOL (Fiep Bulletin - online, 2017)
The present study aimed to investigate and analyze the importance of play in elementary school to a publicschool of Ji-Parana - RO, basing itself on the consideration that the process of teaching and learning should be an enjoyableprocedure for students and teachers. The rationale for this work was done through a descriptive, using the technique of usingquestionnaires, which were sent to students and teachers. The theme addresses the importance of play in children's physicaleducation, since the jokes and games are excellent opportunities for mediation between pleasure and knowledge as the playmakes the act of educating a conscious and intentional compromise, since arguably the activities playful constitute one of themost complete cars educational training and school development. It also examines critically the development of lessons, practiceidentifying the teacher if there is the time of applicability of playfulness in their pedagogical practice. However, it was found thatthe teacher, in teaching anxiety of the contents proposed, thinks there is no time for fun and games, because they lack thetheoretical knowledge to base their practice in daily school life. This position requires deep changes in teaching attitudes.Regardless of the conditions that the school and the educational system to provide their teaching practice, it is the responsibilityof every teacher to motivate their classes, making them attractive and pleasant, preparing the child for it to go up constituting acritical subject for their own actions and through in which he lives. For this reason, the deepening of the play is necessary for goodreflection. This form should be introduced increasingly play in school life, giving opportunity for full and effective training of theindividual to take place, giving you a solid foundation for their citizenship.